Correlation between the role of principle with the pedagogical competences of teachers in Vocational School - Nellitawati Nellitawati (Jurnal Konseling dan Pendidikan, 2017)
This research examined the role of the headmaster and pedagogical competences of teacher in Vocational School and also to see the relationship between the two variables. The populations in this research were 72 teacher and 40 samples using proportional stratified random sampling technique. The research used likert scale as instrument. A score of variable leadership of headmaster was 0,907 and pedagogical score of teachers competence was, 897, which mean the instrument was reliable. The data was analyzed by product moment correlation, r score = .33 > = .284 believed r table standard 95%. Research found that there are relationships between the roles of headmaster with the pedagogy competencies of teacher in Vocational School.